Benefits and consequences that stem from the implementation of an integrated system of qualit management in the companies of the public sector (2013)
The entities of the State in search of improving the presentation of his services and satisfying the needs of the citizens, have realized efforts in implementing his systems of Qualit management, for which there was sent the Standard Model of Internal Control MECI 1000:2005 and the Technical Colombian Norm of Management of NTCGP Publishes 1000:2004, the execution of the previous ones they generate benefits for the instituciones of the public sector to internal and external level.